Illocutionary Acts in dr. Tan's Criticism on Free Nutritious Meal Program - Maria, Jessicca; Simamora, Debora Anriyani; Galaska, Candrika; Simangunsong, Miduk Punguan; Putri, Vera Aprilia; Putri, Dian Marisha (Universitas Muhammadiyah Mataram, 2025)
The aim of this study is to identify and analyze the various types and meanings of illocutionary acts in dr. Tan Shot Yen's public criticism of the Indonesian Free Nutritious Meal (MBG) program. The data were gathered using a qualitative-descriptive study design and a transcript of dr. Tan's critical video on TikTok. The analysis was carried out using John R. Searle's (1969) speech act theory, which classified utterances as assertive, directive, commissive, expressive, and declarative acts. The findings revealed a strategic use of illocutionary acts, with assertives (59.1%) dominating in factual arguments and expressives (28.8%) in expressing moral and emotional weight. Directives (8.1%) and commissives (4%) served less frequently to propose solutions and demonstrate personal commitment, although no declaratives were discovered, indicating the speaker's non-authoritarian public perspective. The study concludes that dr. Tan's critique is a sophisticated rhetorical strategy that effectively combines logical appeal, emotional resonance, and actionable advocacy to challenge policy flaws and promote a more equitable nutrition program, which has contributed to a pragmatic understanding of professional criticism in digital public discourse. The aim of this study is to identify and analyze the various types and meanings of illocutionary acts in dr. Tan Shot Yen's public criticism of the Indonesian Free Nutritious Meal (MBG) program. The data were gathered using a qualitative-descriptive study design and a transcript of dr. Tan's critical video on TikTok. The analysis was carried out using John R. Searle's (1969) speech act theory, which classified utterances as assertive, directive, commissive, expressive, and declarative acts. The findings revealed a strategic use of illocutionary acts, with assertives (59.1%) dominating in factual arguments and expressives (28.8%) in expressing moral and emotional weight. Directives (8.1%) and commissives (4%) served less frequently to propose solutions and demonstrate personal commitment, although no declaratives were discovered, indicating the speaker's non-authoritarian public perspective. The study concludes that dr. Tan's critique is a sophisticated rhetorical strategy that effectively combines logical appeal, emotional resonance, and actionable advocacy to challenge policy flaws and promote a more equitable nutrition program, which has contributed to a pragmatic understanding of professional criticism in digital public discourse.